If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 17 = 8x + -1 Reorder the terms: 17 + 6x = 8x + -1 Reorder the terms: 17 + 6x = -1 + 8x Solving 17 + 6x = -1 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 17 + 6x + -8x = -1 + 8x + -8x Combine like terms: 6x + -8x = -2x 17 + -2x = -1 + 8x + -8x Combine like terms: 8x + -8x = 0 17 + -2x = -1 + 0 17 + -2x = -1 Add '-17' to each side of the equation. 17 + -17 + -2x = -1 + -17 Combine like terms: 17 + -17 = 0 0 + -2x = -1 + -17 -2x = -1 + -17 Combine like terms: -1 + -17 = -18 -2x = -18 Divide each side by '-2'. x = 9 Simplifying x = 9
| -10d-10=-10d | | -60x^3+27x^2-3x= | | X^5/6-x^1/6 | | 3x+5+6x-2=4x-7 | | 6n=1.5n | | 8x/5-3=29 | | 1+1a=2 | | 4x+7+y=22 | | 25a^2-49= | | x^2+11x=36 | | 6y-5x=12fory | | 3(x+1)=8(x-2)+6 | | 36x^3+3x^2-18x= | | 2x^2-18xy-5x+45y= | | 2(4x+5)=17 | | 10m-28=72 | | 5+5x=-7+x | | 24xy-20by+18x-15b= | | 3x^2+9x-2x-6= | | a+7b+a+3c= | | (4x+1)(4x+1)=(3x-1)(3x-1) | | 36x+12x^2-12xy= | | 4x-5y+9+2x-y-14= | | 2x(x^4+6x^3+8x^2-6x-9)=0 | | 10(s-4)=-119 | | 15x^2+26x+8= | | 8+k=3 | | 3(2)(2)+2= | | C/20-42=59 | | x+x(x+1)+(x+2)=24 | | 8x+8y=-16 | | 12.9+-2.2= |